School-based Transition Readiness Services for Adolescents with Disabilities. Issue 2 (3rd April 2021) - Pierce, Doris; Spence, Amy; Sakemiller, Lisa; Roberts, Celeste
ABSTRACT: This study of occupational therapy services to students with disabilities, 14 to 16 years of age, demonstrated effectiveness (Pierce, Spence, Sakemiller, & Roberts, 2020 ). The intervention approach was developed by 14 school-based occupational therapy personnel from 10 Midwestern school districts and described using grounded theory. Forty-two students participated, receiving transition assessments and one hour per week of service over two academic years. Interventions emphasized peer-group projects, prevocational exploration, self-determination, and life skills. Additional themes were the unique skills required to serve adolescents, assessment accuracy, managing therapy time, inter-professional collaborations, and pioneering new practices.